The decentralization policy implementation and school performance - Sabile, Cristeta V. (2007)
The study aimed to describe the extent of implementation of the decentralization scheme of the Department of Education particularly how participating school principals performed their functions and responsibilities under the Principal Empowerment Act and its relationship to the achievements of their Grade 6 pupils. Using a researcher-made questionnaire, the principals' self-rating of their performance and the observations made by the teachers were gathered. It was found that principals think they have been performing to the best of their abilities under the Principal Empowerment scheme, as was validated by the participating teachers' ratings of their principal's work. Stakeholders in the division also tried to create a cooperative and supportive atmosphere to ensure that the scheme works in their division.
"May 2007."
Thesis (M.A. Educational Administration)--University of the Philippines Diliman.
Keywords: Schools -- Decentralization -- Philippines -- Marikina City; School management and organization -- Philippines -- Marikina City